2016
DOI: 10.1117/1.jmi.3.1.017002
|View full text |Cite
|
Sign up to set email alerts
|

Active monitoring of formaldehyde diffusion into histological tissues with digital acoustic interferometry

Abstract: Abstract. The preservation of certain labile cancer biomarkers with formaldehyde-based fixatives can be considerably affected by preanalytical factors such as quality of fixation. Currently, there are no technologies capable of quantifying a fixative's concentration or the formation of cross-links in tissue specimens. This work examined the ability to detect formalin diffusion into a histological specimen in real time. As formaldehyde passively diffused into tissue, an ultrasound time-of-flight (TOF) shift of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…To mitigate artifacts arising from this source, a standardized operating procedure was adopted for processing all tissues in this study. First, tissue thickness was limited to 5 mm, which according to common references (50, 51), should allow efficient penetration of fixation within one hour. Second, fixative was incubated with a magnetic stirrer to maximize diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate artifacts arising from this source, a standardized operating procedure was adopted for processing all tissues in this study. First, tissue thickness was limited to 5 mm, which according to common references (50, 51), should allow efficient penetration of fixation within one hour. Second, fixative was incubated with a magnetic stirrer to maximize diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…We found that diffusion occurs radially from the outside in with the center of the tissue requiring significantly longer to become adequately fixed. The diffusivity coefficients calculated with our system were well-correlated with the apparent diffusion coefficients (ADC) of water measured using MRI that indicated orthogonal validation of our method [ 21 •, 59 ].…”
Section: Diffusion Monitoringmentioning
confidence: 84%
“…To address these limitations, we developed a real-time diffusion monitoring system based on measuring the small differences in sound waves, named T ime- O f- F light (TOF) [ 21 •, 59 ]. As passive diffusion drives formaldehyde into the tissue, the change in the TOF signal manifests as a small acoustic TOF delta that is proportional to the amount of fluid exchange (i.e., ex vivo formaldehyde concentration).…”
Section: Diffusion Monitoringmentioning
confidence: 99%
“…To detect the small acoustic phase retardation resulting from formaldehyde diffusion into tissue, we developed a digital acoustic interferometry algorithm that calculated TOF differentials with subnanosecond precision 13. Pairs of 4 MHz focused transducers were spatially aligned and tissue samples were placed near their common foci.…”
Section: Methodsmentioning
confidence: 99%